WASP-92, WASP-93, and WASP-118: transit timing variations and long-term stability of the systems. Issue 3 (8th March 2019) - Gajdoš, Pavol; Vaňko, Martin; Jakubík, Marián; Evans, Phil; Bretton, Marc; Molina, David; Ferratfiat, Stéphane; Girardin, Eric; Guðmundsson, Snævarr; Scaggiante, Francesco; Parimucha, Štefan
Abstract: We studied three exoplanetary systems with transiting planets: WASP-92, WASP-93, and WASP-118. Using ground-based photometric observations of WASP-92 and WASP-93 and Kepler-K2 observations of WASP-118, we redetermined the orbital and physical parameters of these planets. The precise times of all transits were determined. We constructed O–C diagrams of transits and analysed possible transit timing variations. We did not observe any significant deviation from a linear ephemeris for any of the selected exoplanets. We put upper mass limits for other hypothetical planets in these systems. Using long-term numerical simulation, we looked for stable regions where another planet could exist for a long time. We used the maximum eccentricity method for this purpose. We discuss the influence of values of initial inclination and eccentricity on the shape and size of regions of stability.